Correlation between Reading Comprehension and Reading Strategy Used By English Students of FKIP UIR - Andi Idayani (ELT-Lectura, 2019)
Abstract Reading strategies are skills under consideration which closely depend on specific reading contexts as well as reader awareness, control and intention. Strategies refer to mental actions deliberately employed to facilitate a reading process, to enhance reading comprehension and to overcome reading difficulties in order to achieve particular reading goal. The objective of this research is to find out the correlation between students’ reading comprehension and reading strategy used by the third semester of English Students of FKIP UIR. The researcher used a quantitative method. This research was conducted on October 2018. The population of this research was the third semester of English students of FKIP UIR. The sample of this research was 3d which consist of 37 students. The researcher used a questionnaire for reading strategy and reading test for reading comprehension. Based on the research findings, there was a medium correlation between students’ reading strategy used and students’ reading comprehension by the third semester of English students of FKIP UIR. The researcher found that in level significant 5% rxy > rtable = 0.662>0.325. Its means Ha is accepted and H0 is rejected. In another words, there is significant relationship between students reading strategy used and students’ reading comprehension. Keywords: Reading Strategy, Reading Comprehension